Guide of intoxications in Pediatrics (Salud, Arte y Cuidado, 2021)
The objective of this study was to propose a guide on the management of children with herbal and medicinal poisoning directed at the nursing staff in the intensive care unit at the Pediatric University Hospital Dr. "Agustín Zubillaga". The study is framed in the special project modality, supported by a field investigation, quantitative descriptive type. It was constituted by a population of 65 nursing professionals, with a sample of 20 professionals, who with prior informed consent were given a questionnaire-type instrument consisting of three parts, the first with 4 items, the second with 3 items, the third and last with 12 items on a Likert-type scale modified with trichotomous responses. This was validated by three experts who considered it relevant and applicable. Next, the tabulation and analysis of the results were carried out, presenting them in tables and graphs. It was extracted as conclusions that, half of the surveyed personnel do not have knowledge about the symptomatology of intoxication, being necessary the updating of knowledge to increase their cognitive abilities.
Keywords: herbal intoxication; nursing; intensive care